Parental Nutritional Responsibilities for Children Residing in Orphanages - Umar, Umar Haris Sanjaya; M. Raffi Lazuardy (Indonesian Association of Islamic Family Law Lecturers, 2024)
Problem statement: Children are regarded as a mandate bestowed by Allah upon parents, who have a crucial role and responsibility to fulfil all the rights and needs of their offspring. The effective fulfilment of this responsibility by parents is essential for the proper and optimal growth and development of children. Objective: This study was to investigate the nature of parental responsibility towards their children placed in orphanages and to ascertain whether the surrender of children to orphanages constitutes a legal violation. Methods: This research employs a descriptive normative approach, which involves the identification of legal rules, principles, and doctrines to address the legal issues at hand, and systematically describes the nature of responsibility exhibited by parents who entrust their children to the Syubaanul Wathon Orphanage in Tasikmalaya. The study utilises a qualitative research method to gather in-depth insights regarding the issues examined. Results: The findings indicate that parents who relinquish their children to orphanages do not adequately fulfil their responsibilities, thereby constituting a violation of the child's rights to alimentation. Conclusion: The responsibility of parents is absolute without any reason they have to fulfill this responsibility so that handing over a child to an orphanage to be cared for there is considered child neglect even though the parents are unable to afford it. The responsibility of parents is absolute without any reason they have to fulfill this responsibility so that handing over a child to an orphanage to be cared for there is considered child neglect even though the parents are unable to afford it.